2023
DOI: 10.22541/au.167368560.01551482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does side effects of COVID-19 vaccination include changes in menstrual cycle or its associated pre- and post-menstrual symptoms in reproductive-age women: A Multi-centric Observational study in India.

Abstract: Objective: The study was conducted to know the impact of COVID-19 vaccination on menstrual cycle patterns, pre- and post-menstrual symptoms in women aged 18-45 years. Design & Setting: Multicentric observational study conducted in six institutes of national importance in different states of India over one year. Population: A total of 5709 female participants fulfilling inclusion criteria were enrolled. Methods: Data about impact of vaccines (COVISHIELD and COVAXIN) and prior COVID-19 infection on menstrual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This observation can be due to differences in the studied society and race. In addition, in a study performed on 721 participants in India with the aim of investigating menstrual disorders after COVID-19 vaccine administration (Covaxin and Covishield), it was revealed that these disorders were considerably increased after Covaxin administration (15).…”
Section: Discussionmentioning
confidence: 99%
“…This observation can be due to differences in the studied society and race. In addition, in a study performed on 721 participants in India with the aim of investigating menstrual disorders after COVID-19 vaccine administration (Covaxin and Covishield), it was revealed that these disorders were considerably increased after Covaxin administration (15).…”
Section: Discussionmentioning
confidence: 99%
“…Since the launch of the coronavirus disease 2019 (COVID- 19) in December 2019, it has disturbed almost every aspect of lives worldwide with not only remarkable morbidity and mortality, but also crucial social, educational as well as economic challenges [1].…”
Section: Introductionmentioning
confidence: 99%